Bakti Pembersihan Sampah di Ruang Publik Kawasan Bandara DEO Kota Sorong dalam Rangka “World Clean Up Day 2023” - Azwar Rahmatullah; Murni; Azalia Fajri Yasin; Ummi Hanifah Marshush (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Waste in Sorong consists of a mixture of organic and non-organic materials. Based on its categories, Sorong's waste can be classified as plastic, paper/cardboard, glass/bottle, iron/tin, hazardous waste (B3), and organic waste. The purpose of this community empowerment activity is to maintain the beauty of the public space panorama and instill discipline in the disposal of waste among all residents of Sorong. This community engagement activity took place on September 13, 2023, in front of DEO Airport in Sorong City, Southwest Papua Province. The community engagement activities included: (1) Delivering a presentation on the importance of World Cleanup Day; (2) Cleaning up waste around the public areas of DEO Airport; and (3) Collecting waste in bags for weighing. The theme for this activity was "Environmental Cleanup Service in Sorong City in Commemoration of World Clean Up Day 2023." The technical approach for World Cleanup Day this year involved dividing groups into "A, B, G, C" (academics, business, government, and community) within designated "work focus areas" (waste cleanup) spread throughout the DEO Airport area in Sorong City, particularly in public spaces that are central points for waste input. Therefore, the recommendation from this activity emphasizes the importance of avoiding the use of plastic in daily activities that tend to rely on plastic.